Dynamic communication performance of a horizontal midimew connected mesh network - Yahya Hag, Ala Ahmed; Rahman, M.M. Hafizur; Mohd. Nor, Rizal; Tengku Sembok, Tengku Mohd (Convergence Information Society(CIS), 2016)
Horizontal Midimew connected Mesh Network (HMMN) is new proposed hierarchical interconnection network for massively parallel computers which its static network performance was evaluated and indicated to be great. However, the dynamic communication performance of HMMN has not been evaluated yet. Accordingly, the evaluation of dynamic communication performance has been conducted in this paper, using a deadlock- free routing algorithm with 4 virtual channels. The TOPAZ simulator is used for this evaluation using virtual cut-through flow control under uniform traffic pattern. We found that the dynamic communication performance of the HMMN is better than that of TESH network and counter rival MMN.